Blood Urea Nitrogen to Serum Albumin Ratio as A New Prognostic Indicator in Critically Ill Patients with Diabetic Ketoacidosis: A Retrospective Cohort Study - Hang, Tingting; Huang, Jing; He, Guiping; Li, Jin; Tao, Tingting (Experimental and Clinical Endocrinology & Diabetes, 2024)
Objective To investigate the predictive value of the blood urea nitrogen to serum albumin ratio for in-hospital and out-of-hospital mortality in critically ill patients with diabetic ketoacidosis.Methods Data were obtained from the Medical Information Mart for Intensive Care III (MIMIC III) database, and all eligible participants were categorized into two groups based on the BAR cutoff value. Multiple logistic regression analysis was conducted to determine the association between BAR and in-hospital mortality. The Kaplan–Meier (K–M) analysis was performed to evaluate the predictive performance of BAR. Propensity score matching (PSM) was applied to control confounding factors between the low and high BAR groups.Results A total of 589 critically ill patients with diabetic ketoacidosis were enrolled. Patients with diabetic ketoacidosis with a higher BAR level were associated with higher in- and out-hospital mortality (all p<0.001). A significant 4-year survival difference was observed between the low and high BAR groups (p<0.0001). After PSM analysis, two PSM groups (202 pairs, n=404) were generated, and similar results were observed in the K–M curve (p<0.0001).Discussion Elevated BAR levels were associated with an increased risk of in-hospital mortality in critically ill patients with diabetic ketoacidosis, and BAR could serve as an independent prognostic factor in in-hospital and out-of-hospital mortality for patients diagnosed with diabetic ketoacidosis.
Keywords: diabetic ketoacidosis; blood urea nitrogen; albumin; all-cause mortality; MIMIC-III database